Transient Elastography for Detection of Liver Fibrosis in Children With Autosomal Recessive Polycystic Kidney Disease - Wicher, Dorota; Jankowska, Irena; Lipiński, Patryk; Szymańska-Rożek, Paulina; Kmiotek, Jakub; Jańczyk, Wojciech; Rubik, Jacek; Chrzanowska, Krystyna; Socha, Piotr (Frontiers in Pediatrics, 2019)
Abstract Introduction: Congenital hepatic fibrosis (CHF) is invariably present in all patients with autosomal recessive polycystic kidney disease (ARPKD) but is usually clinically asymptomatic. The portal hypertension in the course of CHF develops and progresses over time, so an early detection of liver fibrosis remains crucial. Aim: The aim of the study was to evaluate a predictive value of transient elastography for evaluating liver disease progress in pediatric ARPKD patients. Material and methods: The study group encompassed 21 pediatric patients with ARPKD and 20 healthy children (control group) from The Children’s Memorial Health Institute in Warsaw, Poland. Liver fibrosis was determined by assessing the liver stiffness (LS) with transient elastography (FibroScan®, FS) using size-appropriate probes. In ARPKD group the laboratory findings, results of an abdominal ultrasound examination, and an endoscopic gastroduodenoscopy were also analysed. Results: Compared with healthy controls, patients with ARPKD had significantly increased median LS values (22 kPa vs. 4.25 kPa, p<0.0001). Based on FS results, ARPKD group was divided into two subgroups: patients (n=5) with LS results suggestive of no fibrosis or minimal fibrosis (LS < 6.9kPa, METAVIR fibrosis stage 0-1) and patients (n=16) with LS results suggestive of at least significant liver fibrosis (LS ≥ 6.9kPa, METAVIR fibrosis stage 2-4). In the first subgroup (no fibrosis or minimal fibrosis), all patients had no signs of portal hypertension. In the subgroup with at least significant liver fibrosis, splenomegaly was observed in 87.5% of patients and thrombocytopenia in 69% of patients. An endoscopic gastroduodenoscopy was performed in fifteen out of twenty one ARPKD patients, nine patients (60%) had esophageal varices. All of these patients had LS results suggestive of at least significant liver fibrosis. Conclusions: TE by FibroScan can be used as an additional method for evaluating liver disease progress in pediatric ARPKD patients.